KESIAPAN GURU SEKOLAH DASAR DALAM PELAKSANAAN PEMBELAJARAN MATEMATIKA YANG BERBASIS PENDIDIKAN KARAKTER DI KOTA KARAWANG JAWA BARAT: Mathemathics learning, Character education - Drs. H. Ramlan M.Sn.; Vevi Hermawan (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2017)
Matemathic learning process which involve moral knowing, moral feeling, and moral action will produce intelligent and characterless nation. This really depends on the teacher, because the character education implementation should start from the class. This research aim to find of the elementary school’s teachers readiness, on mathematics learning implementation which based on character education. The research method in this research used descriptive analysis cualitative, with focus group discussion as the data collection technique. Viewed from the knowledge aspect and the readiness of the teacher on teaching matemathics, can be concluded that the elementary school teacher are not ready to implement the matemathics learning process which based on character education. The elementary school teachers are recommended to improve their competences by doing some study of the concepts and policies which is related to the character education development. The concept and the policies are : Kebijakan Nasional Pembangunan Karakter Bangsa Tahun 2010-2025; Desain Induk Pendidkan Kaakter Tahun 2010; and Pengembangan Pendidikan Budaya dan Karakter Bangsa Tahun 2010.